PENERAPAN ANALISIS SWOT DAN PENDEKATAN 4A SEBAGAI STRATEGI PENGEMBANGAN DESTINASI WISATA DI PULAU ANGSO DUO PARIAMAN - Supardi; Zakia Ayu Lestari; Okki Kurnia (JURNAL MEKAR, 2022)
This article aims to determine tourist perceptions about the components of tourism destinations on Angso Duo Island, Pariaman City. This article uses a SWOT analysis while simultaneously using the 4 A approach (attractions), accessibility (accessibility), amenities (amenities or facilities), and ancillary services (tourism support services). has been comprehensive on Angso Duo Island, and the findings in particular are the development of Angso Duo Island using SWOT analysis as well as 4A. The drawbacks on this island are that it has not been managed with good management, and some of the existing facilities are inadequate. The tourism development strategy is carried out using the SWOT matrix and explain in detail the results of the 4A interview of each informant.